Computational Study of Household Plants as Immunomodulators on Human Metapneumovirus - Raizma, Elda Zaelita Nurul; Sopian, Devia Angelina; Alifianto, Handika Maulana; Yahya, Jasmine Rizkyta; Bimantoro, Tanaya Aryo Jalu; Eshananda, Yuriza (Departemen Kimia, 2026)
Human metapneumovirus (HMPV) is a causative agent of acute lower respiratory tract infections, especially in children. Until now, there are not many natural-based immunomodulatory therapies available. This study aims to explore the potential of household plants from the Syzygiumand zingiber Genus as immunomodulators against HMPV using computational studies. The target receptor used is RNA-dependent RNA polymerase (RdRp), a vital enzyme in HMPV genome replication. The methods used include molecular docking, validation of biological activity through Way2Drug and evaluation of pharmacokinetic feasibility using Lipinski’s Rule of Five. Based on the docking results, the compounds with the strongest binding affinity are myricetin (-8.3 kcal/mol) from the Syzygiumgenus and 10-gingerdione (-7.2 kcal/mol) from the Zingiber genus. Based on the Way2Drug assay results, myricetin compounds from the Syzygiumgenus showed the strongest antioxidant potential (Pa 0.924). In the Zingiber Genus, the compound 10- gingerdione showed the highest antiviral value (Pa 0.434). Based on the Lipinski’s Rule of Five analysis, quercetin from the Syzygiumgenus and 10-gingerol from the Zingiber genus fulfilled all five criteria. Both showed high potential as natural immunomodulatory agents against HMPV, confirming that secondary metabolites from household plants deserve further research as natural immunomodulators.